INCREASING PROFITABILITY OF A MANUFACTURING COMPANY BY USING THE TOTAL PRODUCTIVE MAINTENANCE APPROACH: A REVIEW - Risonarta, Victor Yuardi; Wardhani, Angelia Kusuma (Mechanical Engineering Department, Engineering Faculty, Brawijaya University, 2023)
In the modern world, a company pays serious attention to productivity and efficiency. Several sectors in the manufacturing world are starting to carry out business transformation, particularly those leading to industry 4.0. This circumstance is driven by efforts to achieve higher productivity and an efficient process, mainly after being economically hit by the Covid-19 pandemic. To maintain efficiency, a manufacturing company should maintain its machine and equipment. Total productive maintenance is a system based on the concept of preventive and predictive maintenance. It is designed to prevent loss resulting from many factors, e.g. production interruption due to failures and adjustments, speed loss due to minor stops and speed reductions, and loss due to defects. Total productive maintenance also provides a tool to measure the level of effectiveness of a machine, i.e., overall equipment effectiveness. This review article focusses on the application of total productive maintenance and overall equipment effectiveness to determine the effectiveness of equipment and eliminate the factors that affect the effectiveness of the equipment.